2019
DOI: 10.1089/lrb.2018.0012
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Elastography in Diagnosis and Staging of Breast Cancer-Related Lymphedema

Abstract: SWE should be a useful tool in diagnosis and distinguishing early and late stages of lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In our study, the forearm and arm stiffness values for the affected limbs of patients with clinical lymphedema were significantly higher than those of the contralateral limbs. The main difference between this study and that of Erdogan Iyigun et al was that their study focused on patients with clinical lymphedema (stages 1 and 2), and this study focused on both clinical and latent lymphedema.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In our study, the forearm and arm stiffness values for the affected limbs of patients with clinical lymphedema were significantly higher than those of the contralateral limbs. The main difference between this study and that of Erdogan Iyigun et al was that their study focused on patients with clinical lymphedema (stages 1 and 2), and this study focused on both clinical and latent lymphedema.…”
Section: Discussionmentioning
confidence: 88%
“…Hayashi et al reported a moderate positive correlation between strain elastography and indocyanine green lymphography, which is used for diagnosing lymphatic obstructions. The data on the use of SWE for the diagnosis of lymphedema are limited . Chan et al found the SWV of the cutaneous and subcutaneous tissue of limbs with lymphatic obstruction to be significantly greater than that of unaffected limbs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations